Deficits in the pitch sensitivity of cochlear-implanted children speaking English or Mandarin - Deroche, Mickael L. D.; Lu, Hui-Ping; Limb, Charles J.; Lin, Yung-Song; Chatterjee, Monita (Frontiers in Neuroscience, 2014)
Sensitivity to complex pitch is notoriously poor in adults with cochlear implants (CIs), but it is unclear whether this is true for children with CIs. Many are implanted today at a very young age, and factors related to brain plasticity (age at implantation, duration of CI experience, and speaking a tonal language) might have strong influences on pitch sensitivity. School-aged children participated, speaking English or Mandarin, having normal hearing (NH) or wearing a CI, using their clinically assigned settings with envelope-based coding strategies. Percent correct was measured in three-interval three-alternative forced choice tasks, for the discrimination of fundamental frequency (F0) of broadband harmonic complexes, and for the discrimination of sinusoidal amplitude modulation rate (AMR) of broadband noise, with reference frequencies at 100 and 200 Hz to focus on voice pitch processing. Data were fitted using a maximum-likelihood technique. CI children displayed higher thresholds and shallower slopes than NH children in F0 discrimination, regardless of linguistic background. Thresholds and slopes were more similar between NH and CI children in AMR discrimination. Once the effect of chronological age was extracted from the variance, the aforementioned factors related to brain plasticity did not contribute significantly to the CI children’s sensitivity to pitch. Unless different strategies attempt to encode fine structure information, potential benefits of plasticity may be missed.